Pengaruh Earnings Management terhadap Firm Value melalui Financial Performance sebagai variabel intervening pada perusahaan yang terdaftar di LQ 45 - Selvi Oktavani; Devie Devie Devie (Business Accounting Review, 2017)
This study aimed to examine the influence of earnings management to firm value through financial performance as an intervening variable. Earnings management measured by using discretionary accruals, firm value measured by using Tobin’s Q and financial performance measured by using ROA. This study was conducted on miscellaneous industry firms in Indonesia in the period of 2012 to 2015 with a total sample of 48 firm years.The results of this research indicated a negative and significant influence of earnings management to financial performance. Earnings management had a negative and significant influence to firm value. Financial performance had a positive and significant influence to firm value.